A Proposal of Information Literacy Concept in Accordance with the Context of Higher Education in Vietnam - Xuan Huy, Nghiem; Thi Thanh Huyen, Bui (VNU Journal of Science: Policy and Management Studies, 2022)
Information literacy is a type of personal capacity, which demonstrates an individual’s ability to master the information world, exploit and use information effectively to deal with his/her living, studying and working needs. Information literacy is associated with the development of lifelong learning capacity and social inclusion for individuals. Therefore, information literacy has become increasingly important, becoming a popular topic in education research, especially in the current context of the 4th Industrial Revolution. Since the 70s of the 20th century, information literacy has been widely discussed and developed by educational institutions, especially higher education ones, in Western countries. Concepts, theoretical frameworks and practices for developing information literacy for learners have been established and mostly applied in Western countries. However, with a different educational context, such as the one in Vietnam, how should information literacy for university students be conceptualized and developed? This paper firstly presents an overview of how the concept of information literacy has been changed globally and those aspects that impact the way information literacy has been conceptualized and developed. Key points discussed are educational context, academic culture, teaching and learning practices. From that analysis, the paper proposes a concept of information literacy for students, which is in accordance with the academic culture of Vietnamese higher education.